Phytoplankton Ecology During a Spring-Neap Tidal Cycle in the Southern Tidal Front of San Jorge Gulf, Patagonia - Flores Melo, Elizabeth Ximena (2018)
Tidal fronts are interfaces that separate stratified from mixed waters. The stratified surface zone of a front has lower inorganic nutrient concentrations than the mixed side, and thus, phytoplankton assemblages are expected to differ from one side of the front to the other. Here, we characterize the physics, nutrient dynamics, and biology of the southern front in San Jorge Gulf (SJG), Argentina, during a spring-neap tidal cycle. Baroclinic instabilities influence the shape and position of the front and presumably play an important role in the horizontal transport across the front. The highest phytoplankton biomass concentrations were found in the waters of the stratified side of the front during neap tide, with picophytoplankton, cyanobacteria, and nanophyto-plankton being the main contributors to the total autotrophic biomass. Bacteria contribute the most to heterotrophic biomass. In contrast, during spring tide, the carbon contribution of microphytoplankton was higher than during neap tide. In the mixed side, cells photoacclimate to optimum light conditions, suggesting that cells near the surface, which are probably photoinhibited, and cells below the euphotic zone, which are light-limited, are quickly advected by turbulent vertical motions to depths with optimal irradiance conditions.